An Intrasheath Separation Technique for Nerve-Sparing High Ligation of the Inferior Mesenteric Artery in Colorectal Cancer Surgery - Zheng, Zhifang; Wang, Xiaojie; Huang, Ying; Lu, Xingrong; Zhao, Xiaozhen; Chi, Pan (Frontiers in Oncology, 2021)
Purpose: To investigate the relationship between the left trunk of the inferior mesenteric plexus (IMP) and the vascular sheath of the inferior mesenteric artery (IMA) and to explore anatomical evidence for autonomic nerve preservation during high ligation of the IMA in colorectal cancer surgery. Methods: We evaluated the relationship in 23 consecutive cases of laparoscopic or robotic colorectal surgery with high ligation of the IMA at our institute. Anatomical dissection was performed on 5 formalin-fixed abdominal specimens. A novel anatomical evidence-based operative technique was proposed. Results: Anatomical observation showed that the left trunk of the IMP was closely connected with the IMA and was involved in the composition of the vascular sheath. Based on anatomical evidence, we present a novel operative technique for nerve-sparing high ligation of the IMA that was successfully performed in 45 colorectal cancer surgeries with no intraoperative complications and satisfactory postoperative urogenital functional outcomes. Conclusion: The left trunk of the IMP is involved in the composition of the IMA vascular sheath. This novel anatomical evidence-based operative technique for nerve-sparing high ligation of the IMA is technically safe and feasible.